Quick and Inexpensive Method to Elaborate Tissue Punches Useful in Paraffin Tissue Microarrays - García Garza, Rubén; Rodríguez Vidales, Edgar Paolo; Soto Domínguez, Adolfo (2013)
The tissue microarrays (TMAs) were first called multitumor block. In 1998 was described the current technique, that uses an innovated sampling method for more than 1,000 cylindrical paraffin tissue core biopsies in a single paraffin block. TMAs are now considered as a useful powerful research tool in Histology and Pathology laboratories, for the standardization of immunohistochemical techniques along with in situ hybridization. However, one disadvantage to its widespread use is the high cost of professional paraffin tissue punches, and the complexity in the development of homemade devices previously described in other studies. This study describes a step by step process to develop four different home-made devices made with materials that are common in hospitals and offices. These devices are useful in Histopathology laboratories to obtain paraffin blocks with until 360 samples of tissue, investing from two to fifteen dollars in the development of each device described.